Effect of continuous versus on-demand treatment of ankylosing spondylitis with diclofenac over 2 years on radiographic progression of the spine: results from a randomised multicentre trial (ENRADAS). Issue 8 (4th August 2015) - Sieper, Joachim; Listing, Joachim; Poddubnyy, Denis; Song, In-Ho; Hermann, Kay-Geert; Callhoff, Johanna; Syrbe, Uta; Braun, Jürgen; Rudwaleit, Martin
Abstract : Background: To date, only a single controlled trial provided evidence that non-steroidal anti-inflammatory drugs (NSAIDs) given continuously reduce radiographic progression compared with an on-demand therapy over 2 years in patients with ankylosing spondylitis (AS). In the current study, we tested whether such an effect of NSAIDs could be confirmed in another randomised trial. Methods: Patients with AS were randomised for treatment with either continuous (150 mg/day) or on-demand diclofenac for 2 years. Tumour necrosis factor-blocker treatment was not allowed during the entire study period. The primary outcome was the difference in radiographic progression in the spine as measured by the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) scored by two readers blinded to treatment arm and time point. Results: 62 of 85 patients enrolled in the continuous arm and 60 of 82 enrolled in the on-demand arm completed the study. The mSASSS progression was numerically higher in the continuous group (1.28 (0.7 to 1.9) vs 0.79 (0.2 to 1.4)) (p=0.39). If only patients were analysed who were either C reactive protein positive or had syndesmophytes at baseline, there was again a higher radiographic progression in the continuous versus the on-demand group: 1.68 (0.7 to 2.6) vs 0.96 (0.0 to 1.9) and 2.11 (1.1 to 3.1) vs 0.95 (0.0 to 1.9), respectively. There was no difference between the two treatment groups regarding adverse events. Conclusions: In our study, continuous treatment with diclofenac over 2 years did not reduce radiographic progression compared with on-demand treatment in AS. Trial registration numbers: EudraCt-no 2007-007637-39; ClinicalTrials.gov NCT00715091 .